1987
DOI: 10.1152/ajpregu.1987.252.1.r1
|View full text |Cite
|
Sign up to set email alerts
|

Natriuresis induced by localized perfusion within the third cerebral ventricle of sheep

Abstract: Push-pull perfusion was performed at four different sites in the third cerebral ventricle of conscious sheep. The recovery of the infused solution was 75-90%, suggesting a localized change in the ionic composition and osmolality restricted to a relatively small area in the cerebrospinal fluid (CSF). Sodium and potassium excretion and urine flow were studied before, during, and after perfusion of 200, 150, and 100 mM Na-CSF. Localized perfusion in the anterior dorsal third ventricle (AD3V) of 200 mM Na-CSF caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…In the previous studies, the osmotic challenge was always achieved by manipulating [Na ϩ ] out , in either the extracellular solution (Travis and Johnson, 1993) or the extracellular fluid compartment (Honda et al, 1990 (Cox et al, 1987;Park et al, 1989;Denton et al, 1996). We now provide evidence for functional Na ϩ sensors in the MnPO that likely belong to a complex neuronal network of interconnected structures within the lamina terminalis (Honda et al, 1990;Oldfield et al, 1991Oldfield et al, , 1992McKinley et al, 1999;McKinley et al, 2003).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…In the previous studies, the osmotic challenge was always achieved by manipulating [Na ϩ ] out , in either the extracellular solution (Travis and Johnson, 1993) or the extracellular fluid compartment (Honda et al, 1990 (Cox et al, 1987;Park et al, 1989;Denton et al, 1996). We now provide evidence for functional Na ϩ sensors in the MnPO that likely belong to a complex neuronal network of interconnected structures within the lamina terminalis (Honda et al, 1990;Oldfield et al, 1991Oldfield et al, , 1992McKinley et al, 1999;McKinley et al, 2003).…”
Section: Discussionmentioning
confidence: 61%
“…Fluctuations in plasma and CSF [Na ϩ ] not only trigger short-term adjustments, such as the release of antidiuretic and natriuretic hormones from the neurohypophysis (Bourque et al, 1994;Hussy et al, 2000;Voisin and Bourque, 2002), but also long-term regulation that controls thirst and specific appetite for salt (Weisinger et al, 1979(Weisinger et al, , 1982Denton et al, 1996). It has been hypothesized that specific brain Na ϩ sensors initiate sodium intake (Weisinger et al, 1979;Denton et al, 1996) as well as natriuresis (Cox et al, 1987;Denton et al, 1996), and the recent discovery of coincident detectors of extracellular fluid osmolarity and [Na ϩ ] in the supraoptic nucleus (SON) established the cellular basis for Na ϩ detection in this nucleus (Voisin et al, 1999;Voisin and Bourque, 2002). However, physiological experiments indicated the presence of Na ϩ sensors in the periventricular region of the brain (Cox et al, 1987;Park et al, 1989;Denton et al, 1996), and recent molecular biology data combined with behavioral studies revealed that Na ϩ sensors located in the preoptic region were associated with salt intake (Watanabe et al, 2000;Hiyama et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presumably, specific sodium-sensitive receptors, which primarily are influenced by the sodium concentration of the cerebrospinal fluid (CSF), are located in close proximity to the third brain ventricle and mediate the effects of central high NaCl. 5 However, it is still unclear how periventricular sodium receptors are being activated and/or regulated.…”
Section: Role Of Brain Ouabainlike Compound Inmentioning
confidence: 99%
“…Because Na homeostasis is essential to life, Na-ion concentrations in plasma and CSF are continuously monitored to maintain a physiological level of Na in body fluids. A specific Na sensor has been long hypothesized to exist in the brain for the control of Na intake (Denton et al, 1996;Weisinger et al, 1979) as well as natriuresis (Cox et al, 1987;Denton et al, 1996). The site for the sensing was postulated in the circumventricular organs (CVOs) in the periventricular region of the brain (Cox et al, 1987;Denton et al, 1996;Park et al, 1989).…”
Section: General Introductionmentioning
confidence: 99%